2024
DOI: 10.1021/acs.energyfuels.3c04436
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on the Effect of Molecular Structure Characteristics of Asphaltene on the Synergistic Modification with EVA on Model Waxy Oil

Xue Xia,
Huimin Shi,
Chuanxian Li
et al.

Abstract: The phenomenon of synergistic improvement of the low-temperature rheology of waxy oil between asphaltenes and polymer pour point depressants has been widely reported. However, there has been limited systematic investigation into the variations in synergistic effects among different asphaltenes and pour point depressants. In this study, asphaltenes were extracted from crude oils originating from four distinct blocks, and their impacts on the low-temperature rheological and exothermic characteristics of undoped/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that asphaltene is the natural pour point depressant (PPD), and thermal treating at relatively high temperatures (60–80 °C) is necessary to activate the pour point depressing ability of asphaltene. However, there is still controversy over the mechanism of asphaltene: on the one hand, colloidal asphaltene can provide large amounts of nucleation templates for paraffin wax, thereby enhancing the WAT of waxy crude oil and generating numerous small wax particles; on the other, the cocrystallizing effect between asphaltene and paraffin wax may be more dominant than heterogeneous nucleation, resulting in a reduction in WAT and the generation of large wax aggregates with a small number. , The reason for the difference is related to the molecular structure and the dispersing state of asphaltene. , Research by Xia et al showed that the asphaltene molecules with higher methylene content and lower heteroatom content can fully participate in the cocrystallization process with paraffin, thereby having a stronger effect on improving the rheology of waxy crude oil. In addition, Xia et al altered the dispersing state of asphaltenes by changing the solvent composition and then investigated the effect of asphaltenes’ dispersing state on the rheology of a model waxy oil.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that asphaltene is the natural pour point depressant (PPD), and thermal treating at relatively high temperatures (60–80 °C) is necessary to activate the pour point depressing ability of asphaltene. However, there is still controversy over the mechanism of asphaltene: on the one hand, colloidal asphaltene can provide large amounts of nucleation templates for paraffin wax, thereby enhancing the WAT of waxy crude oil and generating numerous small wax particles; on the other, the cocrystallizing effect between asphaltene and paraffin wax may be more dominant than heterogeneous nucleation, resulting in a reduction in WAT and the generation of large wax aggregates with a small number. , The reason for the difference is related to the molecular structure and the dispersing state of asphaltene. , Research by Xia et al showed that the asphaltene molecules with higher methylene content and lower heteroatom content can fully participate in the cocrystallization process with paraffin, thereby having a stronger effect on improving the rheology of waxy crude oil. In addition, Xia et al altered the dispersing state of asphaltenes by changing the solvent composition and then investigated the effect of asphaltenes’ dispersing state on the rheology of a model waxy oil.…”
Section: Introductionmentioning
confidence: 99%